Development of a differentiated microtubule structure: formation of the chicken erythrocyte marginal band in vivo (The Rockefeller University Press, 1987)
The microtubules of mature nucleated erythrocytes are organized into a marginal band that is confined to a single plane at the periphery and that contains essentially the same number of microtubule profiles in each individual cell. Developing erythrocytes can be isolated in homogeneous and synchronously developing populations from chicken embryos. For these reasons, these cells offer a particularly accessible system for study of the pathway leading to a specific microtubule structure in a normal, terminally differentiated animal cell. Along this developmental course, striking changes occur in the properties of the microtubules. Between the postmitotic cell and the formation of the band, a novel arrangement is found: bundles of laterally associated microtubules in each cell, coursing through the cytoplasm but not confined to the periphery. The microtubule organizing centers evident at early stages disappear by the time the band forms. The microtubules in early cells are readily depolymerized by drugs, but that drug sensitivity is lost in the mature cells. The microtubule arrangement of mature cells is faithfully recapitulated after reversible depolymerization, while that of the immature cells is not. Finally, as the band forms, the microtubules and microfilaments increasingly become coaligned. In sum, the microtubules of immature cells have many properties in common with those of cultured cells, but during maturation those properties change. The results suggest that lateral interactions become increasingly important in stabilizing and organizing the microtubules. The properties of marginal band microtubules, and comparable properties of axonal microtubules, may reflect differences between the requirements for cytoskeletal structures of cycling cells and terminally differentiated cells.